EVAPOTRANSPIRATION TANK (TVAP): A SUSTAINABLE SOLUTION FOR RURAL SANITATION - Rodrigues Maia, Felipe (Journal of Interdisciplinary Debates, 2023)
The following work presents a proposal for rural, sustainable, economic development and aims to demonstrate the advantages of implementing an economically viable system to promote the treatment of domestic sewage in rural areas. This is an exploratory research, carried out from a literature review. The selected method consists of an evapotranspiration tank, which stands out from the others for its simplified feature for segregating black and gray water and for providing sewage treatment. Although it is still considered a rudimentary sewage collection system, the importance of developing proposals for these systems is highlighted, since rural effluents in most cases do not have a correct destination or reuse, generating a large environmental liability. Through reuse processes and the use of low-cost technologies, it is possible to make the effluents innovative products and even use them in the community itself, in order to enhance the organic cultivation of vegetables or forage plants to feed the ruminants of the property and with low production cost, as it is a simple and cheap solution for those farmers who do not have many resources on their property or around their water sources, something that, by the way, is very rare to find, especially in the northeastern semi-arid region. . With the lack of sanitation in rural areas, it is inevitable to obtain by-products and this work proved to be economically viable, with ease of implementation and maintenance accessible to the low-income population, in addition to being an ecologically correct alternative.